Cough-Anal Reflex May Be the Expression of a Pre-Programmed Postural Action - Cavallari, Paolo; Bolzoni, Francesco; Esposti, Roberto; Bruttini, Carlo (Frontiers in Human Neuroscience, 2017)
When coughing, an involuntary contraction of the external anal sphincter occurs, in order to prevent unwanted leakages or sagging of the pelvis muscular wall. Literature originally described such cough-anal response as a reflex elicited by cough, therefore identifying a precise cause-effect relationship. However, recent studies report that the anal contraction actually precedes the rise in abdominal pressure during cough expiratory effort, so that the sphincter activity should be pre-programmed. In recent years, an important family of pre-programmed muscle activities has been well documented to precede voluntary movements: these anticipatory actions play a fundamental role in whole body and segmental postural control, hence they are referred to as anticipatory postural adjustments (APAs). On these basis, we searched in literature for similarities between APAs and the cough-anal response, observing that both follow the same predictive homeostatic principle, namely that anticipatory collateral actions are needed to prevent the unwanted mechanical consequences induced by the primary movement. We thus propose that the cough-anal response also belongs to the family of pre-programmed actions, as it may be interpreted as an APA acting on the abdominal-thoracic compartment; in other words, the cough-anal response may actually be an Anticipatory Sphincter Adjustment, the visceral counterpart of APAs.